The Relationship between the Language of Ancient Northern Inscriptions and Classical Arabic - Akinola Nurudeen Alade (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2024)
Purpose: This paper seeks to explore the similarities between the inscription languages of North Arabia and Classical Arabic, as well as to compare and analyse the differences between them within the framework of linguistic evolution. The study also aims to reveal the relationship between these North Arabian inscriptional languages and Classical Arabic. Design/Methods/Approach: Employing a descriptive-analytical approach, this research presents information and data by linking scientific phenomena and variations through comprehensive interpretation. Field surveys were conducted at the study sites, where inscriptions were documented and their locations determined using advanced software for precise transcription. Findings: The findings of this study underscore the significant historical and cultural connections between the two languages. The linguistic analyses presented highlight both the similarities and mutual influences, thereby enhancing our understanding of how the languages have evolved over time. Research Implications: The implications of this research affirm the historical link between the two languages, recognize the ancient North Arabian inscription languages, and examine their mutual influences. This study enriches our comprehension of the historical and cultural relationship between Classical Arabic and the North Arabian inscription languages, offering new insights into their linguistic evolution and interaction